Numerical Analysis of the Influence of Humidity on the Heat Distribution in Constructional Materials - Pysarenko, Alexander; Vilinskaya, Lyudmila; Burlak, Galina (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2017)
The purpose of this research was to perform numerical simulation of nonstationary temperature fields in isotropic constructional materials with the varied moisture content and study the influence of humidity on the local and integral parameters of temperature redistribution in the specimens. The method of finite differences was used for the numerical computation of the influence of humidity on the heat transfer in some constructional materials. The analytical expression of the characteristic time required for the heating-up of the specimen of a specified thickness to a certain temperature has been derived. The specimen was made of the material with specified heat conductivity and heat absorption coefficients. The derived expression enables a considerable simplification of the procedure used for the introduction of dimensionless parameters with the reduction of errors accumulated in the course of computations. It has been established that the influence of humidity on a change in the temperature with elapse of time at different humidity values in the region near the specimen center can be described by a single modified polynomial. Specified numerical methods enable the investigation of the influence of constructional materials on the coordinate and temporal components of 1D nonstationary temperature field at the local level. The developed software package allows for the variation both of the humidity and the specimen geometry and also the main thermophysical parameters of the specimen during the detailed analysis of the local performances of temperature field.